(untitled) (Journal of Technology and Operations Management, 2016)
An evolving scholarly service system is the ultimate future of e-readers for the academics and research communities. We conceptualize an evolving scholarly service system as socio-technical systems in which people use human assistive technologies to automatically generate summarization of their required information. In this paper, first of all, we showed the global trends of e-readers, human assistive technologies and finally, we proposed an evolving scholarly service system. In this evolving scholarly service system, academics and researchers automatically receive the reading and summarizing services by the scholarly advisory assistants. This paper concludes with practical implications and future research directions.